Peran Agrobacterium Tumefaciens dalam Peningkatan Ketahanan Pangan Tanaman Transjenik Tomat (Solanum Lycoperdicium) - Mardewi; Rifqatul Wafiah; Rachmawati (Mataram University, 2026)
This study aims to examine the role of Agrobacterium tumefaciens-mediated genetic transformation in enhancing the productivity and quality of tomato (Solanum lycopersicum) to support sustainable food security. The review focuses on the optimization of the Ti plasmid system, improvement of T-DNA transfer efficiency, regulation of gene expression through constitutive and inducible promoters, and strategies for post-transformation bacterial control. This research employs a qualitative descriptive method using a Systematic Literature Review (SLR) approach based on PRISMA guidelines. Data were obtained from reputable scientific articles indexed in Scopus and published between 2022 and 2025, and were analyzed through thematic synthesis. The findings indicate that Agrobacterium-mediated transformation results in stable gene integration with consistent Mendelian inheritance patterns across generations. Applications in transgenic tomatoes demonstrate increased fruit number and weight, enhanced lycopene and vitamin content, delayed ripening processes, and improved resistance to both biotic and abiotic stresses. Post-transformation control methods, such as bacteriophage application and quorum sensing inhibition, have been shown to improve biosafety and efficiency. Overall, this study confirms that the optimization of Agrobacterium tumefaciens-based genetic transformation systems consistently produces stable gene integration, enhances tomato productivity and fruit quality, and strengthens resistance to environmental stresses, making it an effective and applicable approach for developing transgenic crops to support sustainable food security.